PENATALAKSANAAN HOLISTIK PADA LANSIA USIA 68 TAHUN DENGAN TUBERKULOSIS PARU DENGAN PRINSIP PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS RAWAT INAP WAY KANDIS - Ayu Anggraini (Jurnal Medika Hutama, 2023)
Background: Tuberculosis is a type of infectious disease which is still a health problem in developing countries, including Indonesia. WHO states that in 2019 tuberculosis cases are expected to reach 10 million cases with 44℅ cases in the Southeast Asia region. In Indonesia, in 2020 the number of tuberculosis cases found was 543,874 cases, this figure slightly decreased when compared to 2019 where there were 566,623 cases found. Meanwhile, the number of Tuberculosis cases in Lampung Province in 2020 reached 16,006 cases with a case discovery rate of 54.6%. Objective: Application of holistic management with family doctor service approach by identifying risk factors, clinical problems, management and prevention of disease in patients based on a problem-solving framework with patient-centered, community-oriented and family-oriented approach. Method: This study is a case report analysis. Primary data is taken from autoanamnesis and alloanamnesis, physical examination, and visits to the patient's home. Secondary data was taken from patient medical records. Results: Based on holistic diagnosis. The patient is diagnosed with pulmonary tuberculosis and has internal risk factors in the form of a lack of knowledge about tuberculosis transmission and behavior to prevent transmission. Visits were made 3 times. Evaluation results show clinical improvement, and changes in patient and family behavior. Conclusion: Holistic management with the principles of family medicine is effective in providing clinical improvement and changes in patient and family behavior.